Oppositional Decoding Influences under Stuart Hall: A Case Study of the Advertisement “The NFL is for everyone” - Daniel Blanchett; Jony Oktavian Haryanto; Jhanghiz Syahrivar (President University, 2023)
Social Justice Content Marketing (SJCM) presents unique challenges to the marketer beyond the traditional marketing tools used to message the consumer effectively. Consumers demand that corporations take action on social issues, yet it is difficult for consumers to define for corporations or marketers what such actions should entail or whether initiatives are effective from the corporate and societal dimensions. Over the last thirty years, changes in media have divided consumer attention across multiple media channels, and message persistence is decreased due to increased message volumes overall. Positioning of SJCM messages is often unintended. Identity via labeling, the backbone of traditional marketing segmentation, targeting, and positioning, is counterproductive in SJCM communications. We used a netnographic approach to capture responses to the National Football League’s SJCM advertisement Football is for Everyone to determine why consumers rejected the advertisement. We applied Stuart Hall’s reception theory to categorize consumer responses and used social dominance theory, labeling and identity frameworks, and semiotics under Pierce. In addition, we examined the benefit to corporate revenue and societal improvement. The results found were that advertisement rejection was due to oppositional and denotative decoding resulting from polysemic symbol versus iconic usage and encoding non-socially dominant beliefs as dominant beliefs in the advertisement. Iconographic messaging reduces non-preferred and negotiated decoding. Further, some corporations may benefit from SJCM financially, but others may suffer substantial financial loss. The gains are more tied to the alignment of core customer demographics and existing beliefs with the advertisement and losses with a disconnect with customer beliefs.